Resveratrol inhibits cytokine production in LPS-stimulated RAW264.7 cells potentially through TLR4/MyD88/NF-κB pathway - Nhat, To Minh; Thu Trang, Tran; Nam, Nguyen Trung (Vietnam Journal of Biotechnology, 2023)
Resveratrol is a naturally occurring compound with anti-inflammatory properties. However, the protective molecular mechanisms of resveratrol against LPS-induced inflammation have not been thoroughly known. In the present study, we examined the anti-inflammatory effect of resveratrol in inflammatory model using murine macrophage-like cell RAW264.7 stimulated with LPS. Resveratrol suppressed the production of inflammatory cytokines in LPS-stimulated RAW264.7 cells with the IC50 value as 17.5 ± 0.7 μM for IL-6, 14.2 ± 1.9 μM for IL-10, and 18.9 ± 0.6 μM for TNF-α. Gene expression of TLR4, MyD88 and NF-κB were significantly suppressed by resveratrol treatment in LPS-stimulated RAW264.7 cells. In conclusion, the anti-inflammatory property of resveratrol is potentially related to its inhibitory effecton TLR4/MyD88/NF-κB signaling pathway in macrophages.